Lethal events in V79 cells irradiated by low-energy protons and correlations with distribution patterns of energy deposition, radical concentration and DNA damage - Davídková, Marie; Kundrát, Pavel; Štěpánek, Václav; Palajová, Zdenka; Judas, Libor (Applied radiation and isotopes, 2009)
Published survival data of V79 cells irradiated by 0.5-5.0 MeV (7-40 keV/microm) protons have been analyzed with a detailed radiobiological model to estimate the per-track yields of lethal lesions. Their correlations with distribution patterns of deposited energy, radical concentrations and with the yields of specific classes of DNA damage have been studied. The observed correlations indicate a potential interpretation of DNA damage lethal for the cell and the initial physical and chemical processes leading to such damage.
Keywords: Cells; poškození DNA; protony; vztah dávky záření a odpovědi; DNA Damage; Protons; lidé; Cell Survival; Dose-Response Relationship, Radiation; viabilita buněk; Financing, Organized; financování organizované; buněčné linie; Humans; Cell Line; buňky